Household Food Waste: The Meaning of Product’s Attributes and Food-Related Lifestyle - Szymkowiak, Andrzej; Borusiak, Barbara; Pierański, Bartłomiej; Kotyza, Pavel; Smutka, Luboš (Frontiers in Environmental Science, 2022)
The increasing volume and value of food waste is a huge threat to achieving sustainable development, food market stability, human population growth, and people’s well-being. Considering that consumers are responsible for a large degree of food waste, the current study looks at the problem of household food waste from the perspective of both food product attributes and consumers’ lifestyles. Specifically: How do people differ in their food disposal inclination based on their food-related lifestyle and products’ quality attributes? The Total Food Quality Model was applied to describe product attributes (taste, health, process, and convenience) whereas food-related lifestyle was measured with: innovativeness/novelty, information about products/health, convenience, price, taste, local/organic food, and social events. The Choice-Based Conjoint Analysis method, based on 753 participants, was used to assess the importance of individual attributes and levels. Clustering was carried out to identify people with similar preferences: through elbow method and Silhouette value maximization, three customer segments were identified. To investigate the distinct characteristics of these clusters related to food waste, one-way multivariate analysis of variance (MANOVA) was conducted. The obtained results confirm that consumers who overlap in their product attribute preferences also share a food-related lifestyle. The main contribution is the identification of consumer groups and the differences that characterise them in terms of the determinants of behaviour related to the importance of the factors of food products influencing the tendency to waste them.